2018
DOI: 10.1371/journal.pone.0192219
|View full text |Cite
|
Sign up to set email alerts
|

"Are you gonna publish that?" Peer-reviewed publication outcomes of doctoral dissertations in psychology

Abstract: If a doctoral dissertation represents an original investigation that makes a contribution to one’s field, then dissertation research could, and arguably should, be disseminated into the scientific literature. However, the extent and nature of dissertation publication remains largely unknown within psychology. The present study investigated the peer-reviewed publication outcomes of psychology dissertation research in the United States. Additionally, we examined publication lag, scientific impact, and variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
37
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 37 publications
2
37
1
1
Order By: Relevance
“…This may be because the graduate either did not attempt to submit manuscripts of their work or was unsuccessful in doing so. However, the proportion of PhD graduates with unpublished dissertation research in our sample was significantly lower than what has been reported by others both in nursing (Kearney, ) and in other fields such as psychology (Evans, Amaro, Herbert, Blossom, & Roberts, ), where the proportions of unpublished dissertations were 76% and 74.4%, respectively. An unpublished dissertation is a lost opportunity for both the graduate and the scientific community at large because research findings reported in dissertations are less likely to be cited in academic journals (Thomas, ) or included as part of systematic reviews of literature (Moyer, Schneider, Knapp‐Oliver, & Sohl, ).…”
Section: Discussioncontrasting
confidence: 84%
“…This may be because the graduate either did not attempt to submit manuscripts of their work or was unsuccessful in doing so. However, the proportion of PhD graduates with unpublished dissertation research in our sample was significantly lower than what has been reported by others both in nursing (Kearney, ) and in other fields such as psychology (Evans, Amaro, Herbert, Blossom, & Roberts, ), where the proportions of unpublished dissertations were 76% and 74.4%, respectively. An unpublished dissertation is a lost opportunity for both the graduate and the scientific community at large because research findings reported in dissertations are less likely to be cited in academic journals (Thomas, ) or included as part of systematic reviews of literature (Moyer, Schneider, Knapp‐Oliver, & Sohl, ).…”
Section: Discussioncontrasting
confidence: 84%
“…Similar results have also been found in public health trainees in the UK (Donaldson & Cresswell, 1996). However, in contrast to our findings for the publication of doctoral dissertations (57.1%), Sipahi et al (2012) reported that only 24.7% of Turkish public health doctoral dissertations were published, and in the USA, Evans, Amaro, Herbert, Blossom, and Roberts (2018) reported that only 25.6% of doctoral dissertations in psychology were converted into publications. Our findings could be skewed by the fact that our data collection process was based on participation, while other studies scanned academic databases.…”
Section: Discussionsupporting
confidence: 79%
“…However, in contrast to our findings for the publication of doctoral dissertations (57.1%), Sipahi et al . (2012) reported that only 24.7% of Turkish public health doctoral dissertations were published, and in the USA, Evans, Amaro, Herbert, Blossom, and Roberts (2018) reported that only 25.6% of doctoral dissertations in psychology were converted into publications.…”
Section: Discussionmentioning
confidence: 99%
“…The latter finding seems to be aligned with previous reports across other disciplines about the proportion of these clinical/applied-oriented dissertations that do not get published in indexed journals [ 91 ]. An explanation of this situation goes beyond the scope of this review, but it has been noted that applied dissertations/theses often do not get published because the authors do not have expectations of careers in academia, where publications are valued [ 91 , 92 ].…”
Section: Discussionmentioning
confidence: 99%